Contribution of income from forest products among selected rural communities in Peninsular Malaysia - Mohd, Rusli; Arzemi, Nur Hafizah (Jabatan Perhutanan Semenanjung Malaysia, 2010)
This paper reports the findings of four studies which attempt to understand the income dependency of rural communities on forest products. Three of the studies surveyed Orang Asli communities, two in Pahang and one in Perak. The fourth study was done on Malay communities in Dungun, Terengganu. Altogether about 500 respondents in more than 20 villages were surveyed. In all the studies, data were gathered by interviewing the respondents face-to-face using prepared structured questionnaires. Gathering and selling of forest - products is still the main economic activity of a big proportion of the Orang Asli, however, agriculture is the main source of income of the rural Malay communities. The findings reveal that income from forest products, notably plants, contributes on the average about 40% to 65% of the household income of the Orang Asli. There is evidence which suggests that giving the Orang Asli other income opportunities will make them less dependent on forest products. Other results show that only one in five of rural Malay households are involved in collecting and selling forest products. Furthermore, income from forests contributes only about 25% of their household incomes. The implications of these findings on the sustainability of forest as well the rural communities will be briefly discussed.